A theology of political vocation : Christian life and public office - Senior, John E., 1977- (Waco, Texas : Baylor University Press, 2015)
Power, money, endless competition. A zero-sum game. Politics as usual. Only the hearty or craven need apply. The political actors have lost sight of the politics of a common good. A Theology of Political Vocation takes up the question of public life precisely where most discussions end. Proving that moral ambiguity does not exclude moral possibility, author John Senior crafts a theology of political vocation not satisfied simply by theologies of sin and grace and philosophical theories of power. For Senior, political theology moves beyond merely staking a claim within a public conversation, a move that prizes discursive skills and aims at consensus concerning shared norms and values. Political theology must offer an account of a political vocation. Senior connects political deliberation to moral judgment, explores use and consequence of power, analyzes political conflict and competition, and limns the ethics of negotiation and compromise. In light of this richer understanding of political vocation, Senior develops theological resources appropriate to a variety of ecologies -- ordinary citizens, political activists, and elected officials. A Theology of Political Vocation shows how Christian politicians can work faithfully within the moral ambiguity of political life to orient their work -- and indeed, their very selves -- toward the common good.
Introduction: Statecraft in a Machiavellian age -- What is a political vocation? -- Responsibility and representation -- Vocation and formation in political space -- The moral ambiguity of political space -- The journey of political vocation -- The project of political vocation -- Irony as a political virtue -- Good political competition -- Conclusion: The possibility of political vocation.
Includes bibliographical references (pages 205-219) and index.
Keywords: Vocation -- Christianity; Christianity and politics; Christians -- Political activity; Political science -- Philosophy